AN INVESTIGATION ON THE NON SPESIFIC IMMUNE SYSTEM (MUCOSAL) OF TILAPIA (Oreochromis mosambicus) BASED ON HISTOCHEMICAL ANALYZES - Ruswahyuni .; Pujiono Wahyu Purnomo; Cahyono Purbomartono (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Mucus is one of a non-specific defense mechanism, since this is the first element of aquatic organisms, which contact physically, chemically, or biologically with the environment. The mucus self defense mechanism investigation was carried out on fresh water fish tilapia (Oreochromis mosambicus). Eight (8) types of lectine were used to examine residual carbohydrate-based protein from mucous component based on histological and histochemical observation method. The review was directed as basic information for detail review about physiology adaptation aspects. The results showed that mucous in goblet cells from palatal, gills primary lamella, ecophagus and skin reacted with WGA (Wheat Germ Aglutinin) lectine. In another part, mucous from the goblet cells in palatal and esophagus cells reacted with PNA (Peanut Aglutinin). Based on these results, therefore, it can be concluded that mucous from goblet cells in esophagus contains residual of N-asetil glucosamine and/or similar acid β-galactose and α-N-acetyl galactomine. Mucous from goblet cell in palatal contains residual of X-acetyl glucosamine and/or sialat acid and galactose. While mucous in the gills lamella contains carbohydrate residual, namely N-acetyl glucosamine and/or sialat acid